Epidemiology and Molecular Characterisation of Multidrug-Resistant Escherichia coli Isolated from Cow Milk - Zarin Tasnim Mim; Chandan Nath; Abdullah Al Sattar; Rijwana Rashid; Mehedy Hasan Abir; Shahneaz Ali Khan; Md Abul Kalam; Shahanaj Shano; Rowland Cobbold; John I. Alawneh; Mohammad Mahmudul Hassan (Veterinary Sciences)
Antimicrobial resistance (AMR) is a growing global concern and poses a significant threat to public health. The emergence of multidrug-resistant organisms, including Escherichia coli, also presents a risk of transmission to humans through the food chain, including milk. This study aimed to investigate the prevalence of E. coli in raw milk in the Chattogram metropolitan area (CMA) of Bangladesh and their phenotypic and genotypic antimicrobial resistance patterns. A total of 450 raw cow milk samples were collected from 18 farms within the CMA. The isolation and identification of E. coli were performed following standard bacteriological methods. Antimicrobial susceptibility testing (AST) was conducted using the Kirby–Bauer disc diffusion method. Molecular detection of E. coli and antimicrobial resistance genes was performed using the Polymerase Chain Reaction (PCR). This study found 134 (29.77%) milk samples that tested positive for E. coli. Antimicrobial susceptibility testing (AST) revealed the highest resistance rates (69.40%) to be for ampicillin, amoxicillin–clavulanic acid, cephalothin, and cephalexin, with the lowest resistance (21.64%) being for norfloxacin. A significant correlation (r = 1) was observed between ciprofloxacin and ceftazidime resistance among the antimicrobials tested. All E. coli isolates were classified as multidrug-resistant (MDR), being resistant to three or more antimicrobial classes, with a multiple resistance index >0.2. PCR amplification showed that the blaTEM gene had the highest prevalence (74.19%) among the ESBL and antimicrobial resistance genes tested. In contrast, the blaCMY-1 gene had a lower prevalence (6.45%) among the ESBL genes, while the tetD gene had the lowest prevalence (2.9%) among the resistance genes tested. Positive correlations were observed between antimicrobial resistance and the presence of these resistance genes. This study emphasises the high prevalence of MDR E. coli in raw cow milk and its significant potential impact on public health. It underscores the urgent need for strategic interventions to effectively manage and mitigate AMR in the Bangladeshi dairy sector, focusing on the prudent use of antimicrobials and implementing enhanced AMR surveillance.